EFEKTIVITAS EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP MORTALITAS Plutella xylostella L. PADA TANAMAN SAWI - Hasnah Hasnah (Jurnal Floratek, 2009)
The Effectiveness of Great Morinda Extract toMortality of Plutella Xylostella L. on Green Mustard  Hasnah dan Nasril Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT One of the pests frequently attacking mustard greens is Plutella xylostella. Resulted damage can be up to 58-100% if control is not immediately done, especially in the dry season. The objective of this research was to obtain a effective concentration of great morinda extracts for controlling P. xylostella on mustard green. This research was conducted in Experimental Farm and Laboratory of Plant Pests and Diseases Department at the Faculty of Agriculture Unsyiah Darussalam Banda Aceh.  The results showed that application of great morinda was effective to control P. xylostella. Mortality of 100% larva was recorded at 3 days after application of  great morinda extract in the concentration of 150ml L-1 solution and this was equivalent to 1 ml L-1  of methrin delta solution, and that the percentage of pupa and imago was 0%. The intensity of damage to plant leaf of mustard greens was only 15.47% in the application of 150 ml L-1 of great morinda. It can be concluded that the concentration of 150ml L-1 solution of great morinda fruit extracts was effective for controlling P. xylostella and that was equivalent to 1 ml L-1  of methrin delta solution.